Solid-state electrolyte, method for preparing the same, and solid-state lithium metal battery
Patent Information
- Application Number
- CN202611287153.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]为了解决现有PEO基聚合物固态电解质离子电导率低、热尺寸稳定性不足以及锂金属界面稳定性差的问题,本发明提供一种固态电解质及其制备方法和固态锂金属电池
[0032]1. This invention uses zirconium oxychloride as the zirconium source and benzoic acid as the modifier to prepare defect-controlled fluorinated UiO-66 by a solvothermal method. By using the monodentate coordination regulation effect of benzoic acid, controllable ligand defects are introduced into the MOF framework, which not only maintains the structural stability of fluorinated UiO-66, but also increases the number of active sites in the channels, which is beneficial to improving lithium ion transport efficiency.
Smart Images

Figure CN122931007A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid-state lithium metal battery technology, specifically to a high thermal stability fluorinated UiO-66 / PAN electrospun composite solid electrolyte, its preparation method, and a solid-state lithium metal battery including the electrolyte. Background Technology
[0002] With the rapid development of portable electronic devices, electric vehicles, and large-scale energy storage power stations, the demand for higher energy density and intrinsic safety in electrochemical energy storage systems continues to rise. Traditional commercial lithium-ion batteries rely on liquid organic electrolytes, whose inherent volatility and flammability always bring safety risks such as leakage, combustion, and explosion. At the same time, the narrow electrochemical stability window of liquid electrolytes makes it difficult to adapt to high-capacity lithium metal anodes and high-voltage cathodes, becoming a core bottleneck for further breakthroughs in battery energy density. Against this backdrop, solid-state lithium metal batteries, which completely replace traditional liquid electrolytes with solid electrolytes, are expected to fundamentally resolve the safety hazards of liquid systems. Furthermore, their wider electrochemical window allows for compatibility with high-capacity lithium metal anodes and high-voltage cathodes, making them one of the core development directions for next-generation high-energy-density energy storage devices.
[0003] Among the currently developed solid-state electrolyte systems, solid-state polymer electrolytes have become the most promising technology route for industrial application due to their excellent flexibility, good electrode interface contact, and high compatibility with existing battery processing technologies. Polyethylene oxide (PEO)-based solid-state polymer electrolytes, in particular, are the most widely studied matrix material in the field of polymer electrolytes due to their excellent film-forming ability and superior lithium salt solubility. However, the performance of the PEO matrix still has a significant temperature-dependent drawback: at room temperature and medium-low temperatures, its molecular chain crystallinity is high, significantly limiting chain segment mobility, resulting in generally low room-temperature ionic conductivity, which is difficult to meet the operational requirements of practical batteries; while at higher temperatures, PEO is prone to softening, thermal shrinkage, and dimensional deformation, which not only weakens the electrolyte's mechanical barrier ability but also disrupts the stable contact at the electrode-electrolyte interface, exacerbating interfacial side reactions and the risk of lithium dendrite growth.
[0004] To address the aforementioned performance deficiencies of PEO-based electrolytes, the introduction of functional inorganic fillers to construct composite polymer electrolytes is a mainstream modification strategy that balances ion transport and mechanical properties. Among various inorganic fillers, metal-organic frameworks (MOFs) have gradually become a research hotspot for composite electrolyte fillers due to their designable topologies, well-ordered pore systems, and tunable surface chemistry, which can provide ordered transport pathways for lithium ions and regulate lithium salt dissociation behavior. Zr-based MOF material UiO-66, with its structurally stable Zr-O metal clusters and uniform, well-ordered pore structure, exhibits excellent chemical and thermal stability, enabling it to adapt to the complex environment inside batteries. It can serve as an auxiliary channel for lithium ion transport, effectively optimizing ion migration behavior within the electrolyte. Furthermore, functionalizing UiO-66 with fluorine-containing ligands allows for precise control of the local charge distribution on the filler surface through the high bond energy and strong polarity of the CF bonds. This promotes the full dissociation of lithium salts to increase the concentration of free lithium ions and induces the formation of a stable fluorine-rich interface layer at the interface, simultaneously improving the interfacial and thermal stability of the electrolyte.
[0005] Although modification with a single inorganic filler can specifically improve one or more properties of PEO-based electrolytes, existing research shows that relying solely on discretely distributed filler particles often makes it difficult to simultaneously achieve a synergistic improvement in ionic conductivity, mechanical strength, interfacial stability, and thermal dimensional stability. In particular, it is difficult to solve the problems of high-temperature dimensional deformation and discontinuous ion transport paths at the structural level. Summary of the Invention
[0006] To address the issues of low ionic conductivity, insufficient thermal dimensional stability, and poor lithium metal interface stability in existing PEO-based polymer solid electrolytes, this invention provides a solid electrolyte, its preparation method, and a solid lithium metal battery. This solid electrolyte improves lithium-ion migration capability, membrane thermal stability, and battery cycle stability through the synergistic effect of a defect-regulated fluorinated metal-organic framework, an electrospun PAN fiber backbone, and a PEO / LiTFSI polymer electrolyte phase.
[0007] The specific solution of the present invention is as follows: a solid electrolyte comprising a PAN electrospun nanofiber skeleton, defect-controlled fluorinated UiO-66 particles anchored or dispersed on the PAN (i.e., polyacrylonitrile) electrospun nanofiber skeleton, and a PEO / LiTFSI polymer electrolyte phase filling the pores of the PAN electrospun nanofiber skeleton.
[0008] The defect-regulated fluorinated UiO-66 particles are distributed along the surface of the PAN electrospun nanofiber skeleton or in the interfiber channels, forming a continuous metal-organic framework enriched ion transport interface; the defect-regulated fluorinated UiO-66 particles contain ligand defect sites generated by benzoic acid regulation, and the defect sites provide additional lithium ion adsorption and transport active sites.
[0009] The composite solid electrolyte, after heat treatment in air at 180°C for 2 hours, retains an area of not less than 85%; and its ionic conductivity at 80°C is not less than 1.0 mS·cm. -1 The composite solid electrolyte exhibits an ionic conductivity of not less than 0.07 mS·cm at 30°C. -1 The oxidation stability potential is not lower than 5.5 V.
[0010] A method for preparing a solid electrolyte includes the following steps:
[0011] (1) Zirconium oxychloride, fluorine-containing organic ligands and benzoic acid were added to a mixed solvent, and after solvothermal reaction, separation, washing and drying, defect-controlled fluorinated UiO-66 particles were obtained.
[0012] (2) Defect-controlled fluorinated UiO-66 particles, PAN (i.e., polyacrylonitrile) and a first organic solvent are mixed to obtain an electrospinning precursor solution; the electrospinning precursor solution is electrospinned and dried to obtain an F-UiO-66@PAN porous composite nanofiber membrane.
[0013] (3) Dissolve polyethylene oxide and LiTFSI in a second organic solvent to obtain a polymer electrolyte solution;
[0014] (4) The polymer electrolyte solution is impregnated or cast into the F-UiO-66@PAN porous composite nanofiber membrane and dried to obtain F-UiO-66@PAN@PEO composite solid electrolyte.
[0015] In step (1), zirconium oxychloride is zirconium oxychloride octahydrate, the fluorinated organic ligand is 2,3,5,6-tetrafluoroterephthalic acid, and the molar ratio of benzoic acid to the fluorinated organic ligand is (0.1-0.5):1. More preferably, the molar ratio of benzoic acid to the fluorinated organic ligand is 0.3:1. Benzoic acid, as a monodentate coordination modifier, can introduce controllable ligand defects in the UiO-66 framework, increasing the number of active sites in the pores, thereby promoting the adsorption and transport of lithium ions.
[0016] The mixed solvent is a ternary mixed solvent of N,N-dimethylformamide, water, and acetic acid, with a volume ratio of (4-6):(2-4):(1-3). More preferably, the volume ratio of N,N-dimethylformamide, water, and acetic acid is 5:3:2. This ternary mixed solvent system can regulate the hydrolysis rate of the zirconium source and the dissolution behavior of the ligands, which is beneficial for the formation of defect-controllable fluorinated UiO-66 crystals.
[0017] The solvothermal reaction temperature is 90-120℃, and the reaction time is 18-30 h. More preferably, the reaction temperature is 100℃, and the reaction time is 24 h. These reaction conditions promote the full coordination of the Zr-O cluster with the fluorinated organic ligand, and, with the modulating effect of benzoic acid, form a fluorinated UiO-66 framework structure with appropriate defects.
[0018] Further, after centrifugation, the reaction product in step (1) is washed sequentially with N,N-dimethylformamide and methanol, and then vacuum dried at 70-90°C for 10-16 h; preferably, it is vacuum dried at 80°C for 12 h to remove residual solvent and improve the structural stability of defect-controlled fluorinated UiO-66 particles.
[0019] In the defect-regulated fluorinated UiO-66 particles obtained in step (1), benzoic acid is introduced as a coordination regulator to the defect sites of the missing ligands, with a defect degree of 5%-15%.
[0020] In step (2), the first organic solvent is N,N-dimethylformamide, and the mass ratio of the defect-controlled fluorinated UiO-66 particles, PAN, and the first organic solvent is (1-3):(0.5-1.5):(8-12). More preferably, the mass ratio of the defect-controlled fluorinated UiO-66 particles, PAN, and the first organic solvent is 2:1:10.
[0021] Further, in step (2), the mixing temperature is 40-80℃ and the mixing time is 12-36 h; more preferably, the mixture is stirred at 60℃ for 24 h to fully dissolve the PAN and uniformly disperse the defect-controlled fluorinated UiO-66 particles in the electrospinning precursor solution.
[0022] In step (2), the electrospinning voltage is 2-15 kV, and the distance from the nozzle to the receiver is 10-18 cm. More preferably, a dual voltage condition of 2 kV and 10 kV is used, and the distance from the nozzle to the receiver is 12 cm. Under the above electrospinning conditions, a continuous interconnected nanofiber network can be formed, and the fluorinated UiO-66 particles can be fixed on the surface of the PAN fibers or in the inter-fiber pores.
[0023] In step (2), the fiber membrane obtained after electrospinning is first dried at 50-80°C, and then vacuum dried at 120-170°C. More preferably, it is first dried at 60°C for 2 h, and then vacuum dried at 150°C for 12 h to remove residual solvent and improve the dimensional stability of the fiber membrane.
[0024] In step (3), the second organic solvent is acetonitrile, and the polymer electrolyte solution contains polyethylene oxide and Li + The molar ratio is (8-15):1. A further preferred ratio is 10:1. This ratio can balance lithium salt dissociation, polymer chain movement, and membrane mechanical stability.
[0025] In step (3), polyethylene oxide and LiTFSI are dissolved by stirring at 60-80°C, and then stirred and degassed at 35-50°C. More preferably, the mixture is first stirred at 70°C for 5 h, then stirred at 40°C for 12 h and degassed for 1 h.
[0026] In step (4), the polymer electrolyte solution is impregnated or cast into the F-UiO-66@PAN porous composite nanofiber membrane in an inert atmosphere and dried at 50-70°C to remove the solvent. More preferably, the inert atmosphere is argon or nitrogen to reduce the influence of water and oxygen on the lithium salt and polymer electrolyte. More preferably, drying at 60°C removes acetonitrile, ensuring that the PEO / LiTFSI polymer electrolyte phase is uniformly filled into the F-UiO-66@PAN porous fiber network.
[0027] A solid-state lithium metal battery includes a composite solid-state electrolyte. In a Li||Li symmetric cell, the composite solid-state electrolyte can reduce the polarization voltage during lithium deposition / stripping and suppress lithium dendrite growth caused by local current density unevenness. In a LiFePO4||Li full cell, the composite solid-state electrolyte can maintain a stable charge-discharge plateau and a high capacity retention rate, thereby improving the cycle life and safety of the solid-state lithium metal battery.
[0028] The composite solid electrolyte of this invention comprises a PAN electrospun nanofiber framework, defect-modified fluorinated UiO-66 particles anchored or dispersed on the PAN electrospun nanofiber framework, and a PEO / LiTFSI polymer electrolyte phase filling the pores of the PAN electrospun nanofiber framework. The PAN electrospun nanofiber framework is a continuously cross-linked three-dimensional porous network structure; this three-dimensional porous network structure provides mechanical support for the composite solid electrolyte and provides wetting and fixation space for the polymer electrolyte phase. The defect-modified fluorinated UiO-66 particles are distributed along the surface of the PAN nanofibers or in the interfiber channels, forming a continuous MOF-enriched ion transport interface. The Zr-O clusters and regular channels in the fluorinated UiO-66 provide auxiliary channels for lithium ion migration, and the fluorinated ligands can regulate local polarity and charge distribution, thereby promoting lithium salt dissociation and lithium ion migration. The ligand defect sites generated by benzoic acid regulation further increase the active adsorption sites within the channels, providing more transport sites for lithium ions. The PEO / LiTFSI polymer electrolyte phase is filled in the F-UiO-66@PAN porous composite nanofiber membrane, forming a composite interface with PAN fibers and fluorinated UiO-66 particles. This composite interface helps reduce the resistance to ion migration within the electrolyte and improves the interfacial contact between the electrolyte and the lithium metal anode.
[0029] The composite solid electrolyte of this invention exhibits excellent thermal dimensional stability: after heat treatment in air at 180°C for 2 hours, the area retention rate is not less than 85%. This thermal stability stems from several synergistic effects: firstly, the CF bond has high bond energy, and the introduction of fluorinated ligands significantly increases the thermal decomposition barrier of the MOF framework; secondly, the UiO-66 type Zr-O metal cluster itself possesses excellent thermal stability, and its framework structure exhibits high thermal tolerance; thirdly, the PAN fiber network, acting as a physical support framework, can restrict the flow and shrinkage of the PEO matrix at high temperatures; and fourthly, the interfacial interaction between the fluorinated MOF particles and PEO segments can suppress the thermal motion of the PEO molecular chains, increasing the thermal deformation temperature of the composite system.
[0030] The composite solid electrolyte of this invention exhibits excellent ion conductivity within a temperature range of 30-80℃. As temperature increases, the mobility of PEO chain segments enhances, and the lithium salt dissociation and continuous ion transport channels promoted by fluorinated MOF become more effective at high temperatures, resulting in an ionic conductivity of at least 1.0 mS·cm for the composite electrolyte at 80℃. -1 It can meet the operating requirements of solid-state batteries under high-temperature conditions.
[0031] Compared with the prior art, this application includes at least the following beneficial effects:
[0032] 1. This invention uses zirconium oxychloride as the zirconium source and benzoic acid as the modifier to prepare defect-controlled fluorinated UiO-66 by a solvothermal method. By using the monodentate coordination regulation effect of benzoic acid, controllable ligand defects are introduced into the MOF framework, which not only maintains the structural stability of fluorinated UiO-66, but also increases the number of active sites in the channels, which is beneficial to improving lithium ion transport efficiency.
[0033] 2. This invention constructs a three-dimensional nanofiber support network of PAN by electrospinning. This network can provide a continuous, uniform and porous skeleton structure, improve the mechanical integrity of the composite solid electrolyte membrane, and reduce shrinkage, curling and interface delamination that occur during heat treatment or battery operation.
[0034] 3. This invention fixes defect-controlled fluorinated UiO-66 particles in a PAN fiber network, avoiding the problem of discontinuous ion channels caused by the random aggregation of inorganic fillers in the polymer electrolyte, and constructs a continuous ion transport interface using MOF channels, Zr-O clusters and defect sites.
[0035] 4. This invention modulates the local chemical environment of UiO-66 through fluorine-containing ligands. The high bond energy of the CF bond can not only improve the electrochemical stability of the electrolyte, but also significantly enhance the thermal dimensional stability of the material. At the same time, the defect structure regulated by benzoic acid further enriches the active sites for lithium-ion transport.
[0036] 5. This invention fills F-UiO-66@PAN porous composite nanofiber membrane with a PEO / LiTFSI polymer electrolyte phase, so that the polymer phase, fiber skeleton and fluorinated MOF work synergistically, thereby improving ion transport, interfacial stability and thermal dimensional stability at the same time.
[0037] 6. The F-UiO-66@PAN@PEO composite solid electrolyte obtained in this invention exhibits a strength of not less than 0.07 mS·cm at 30℃. -1 Its ionic conductivity is not less than 1.0 mS·cm at 80℃. -1 It exhibits high ionic conductivity, an oxidation stability potential exceeding 5.5 V, and an area retention rate of no less than 85% after heat treatment at 180℃ for 2 hours. It can also support long-term stable cycling of Li||Li symmetric cells. Attached Figure Description
[0038] The present application will be described in further detail below with reference to the accompanying drawings and preferred embodiments. However, the drawings are only used to explain the present application and should not be construed as limiting the scope of protection of the present application.
[0039] Figure 1 This is a schematic diagram of the preparation process of a solid electrolyte according to the present invention.
[0040] Figure 2This is a schematic diagram of the lithium-ion transport path in the solid electrolyte of the present invention.
[0041] Figure 3 This is a SEM image of the defect-controlled F-UiO-66 particles in Example 1.
[0042] Figure 4 This is a SEM image of the F-UiO-66@PAN composite nanofiber membrane in Example 1.
[0043] Figure 5 The elemental distribution diagram is shown for the F-UiO-66@PAN composite nanofiber membrane in Example 1.
[0044] Figure 6 The images show the XRD patterns of UiO-66 and defect-controlled F-UiO-66 in Example 1.
[0045] Figure 7 The image shows the F 1s XPS plot of F-UiO-66@PAN in Example 1.
[0046] Figure 8 This is a comparison chart of the ionic conductivity of different solid electrolytes in Examples 1-3.
[0047] Figure 9 The images show the electrochemical stability and Tafel curves of different solid electrolytes in Examples 1-3.
[0048] Figure 10 The graph shows the long-cycle performance of the Li||Li symmetric battery in Application Example 1.
[0049] Figure 11 The graph shows the rate cycling performance of the Li||Li symmetric battery in Application Example 1.
[0050] Figure 12 The cycling performance of the LiFePO4||Li full cell in Application Example 4 is shown.
[0051] Figure 13 The diagram shows the thermal dimensional stability of the solid electrolyte membranes in Examples 1-3. Detailed Implementation
[0052] The present application will be further described below with reference to the accompanying drawings. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present application. Equivalent substitutions or conventional adjustments made by those skilled in the art without departing from the technical concept of the present application should be included within the scope of protection of the present application.
[0053] Chemicals and reagents: Zirconium oxychloride octahydrate (ZrOCl2·8H2O), 1,4-phthalic acid, 2,3,5,6-tetrafluoroterephthalic acid, benzoic acid, N,N-dimethylformamide, acetic acid, methanol, acetonitrile, PAN, PEO, and LiTFSI are all commercially available reagents. Unless otherwise specified, the reagents used in the examples are all conventional commercial products.
[0054] Example 1: Preparation of F-UiO-66@PAN@PEO composite solid electrolyte (benzoic acid addition amount 0.3 equivalents)
[0055] Step (1): Preparation of defect-controlled F-UiO-66 particles. 1610 mg of zirconium oxychloride octahydrate (ZrOCl2·8H2O), 1190 mg of 2,3,5,6-tetrafluoroterephthalic acid, and 183 mg of benzoic acid (molar ratio to fluorine-containing ligand approximately 0.3:1) were weighed and added to 50 mL of a ternary mixed solvent with a volume ratio of N,N-dimethylformamide / water / acetic acid of 5:3:2. After thorough stirring to ensure uniform dispersion, the mixture was transferred to a 100 mL stainless steel reactor lined with polytetrafluoroethylene and subjected to a solvothermal reaction at 100 °C for 24 h. After the reaction, the mixture was allowed to cool naturally to room temperature, and the precipitate was collected by centrifugation. The precipitate was washed three times sequentially with N,N-dimethylformamide and methanol to remove unreacted ligands, benzoic acid modifier, and residual solvent. The resulting solid was then vacuum-dried at 80 °C for 12 h to obtain defect-controlled F-UiO-66 particles.
[0056] Step (2): Prepare F-UiO-66@PAN porous composite nanofiber membrane. The defect-controlled F-UiO-66 particles obtained in step (1), PAN, and N,N-dimethylformamide were mixed at a mass ratio of 2:1:10 and stirred at 60°C for 24 h to obtain a uniformly dispersed electrospinning precursor solution with a viscosity suitable for spinning. The precursor solution was placed in an electrospinning apparatus with the nozzle-to-receiver distance set to 12 cm. Electrospinning was performed using dual voltage conditions of 2 kV and 10 kV, allowing F-UiO-66 particles to be deposited synchronously with the PAN fibers to form a porous composite fiber network. After spinning, the resulting composite fiber membrane was dried at 60°C for 2 h, and then vacuum dried at 150°C for 12 h to remove residual solvent and improve membrane structural stability, thus obtaining the F-UiO-66@PAN porous composite nanofiber membrane.
[0057] Step (3): Prepare the PEO / LiTFSI polymer electrolyte solution. Add PEO and LiTFSI to acetonitrile to make the EO:Li +The molar ratio is 10:1. The mixture is first stirred at 70℃ and 500 rpm for 5 h to allow PEO to fully swell and mix evenly with lithium salt. Then, the temperature is reduced to 40℃ and 400 rpm and stirring is continued for 12 h. After that, it is allowed to stand or degassed under vacuum for 1 h to obtain a homogeneous PEO / LiTFSI polymer electrolyte solution.
[0058] Step (4): Prepare F-UiO-66@PAN@PEO composite solid electrolyte. The PEO / LiTFSI polymer electrolyte solution obtained in step (3) is cast onto the F-UiO-66@PAN porous composite nanofiber membrane obtained in step (2) under an argon atmosphere, so that the polymer electrolyte is fully wetted and fills the pores of the fiber network. The sample is then dried at 60°C to remove acetonitrile, and then aged at room temperature to allow the PEO / LiTFSI phase and the F-UiO-66@PAN framework to form a stable composite structure, thus obtaining the F-UiO-66@PAN@PEO composite solid electrolyte membrane.
[0059] Example 2: Preparation of F-UiO-66@PAN@PEO composite solid electrolyte (benzoic acid addition amount 0.1 equivalent)
[0060] Step (1): Preparation of defect-controlled F-UiO-66 particles. 1610 mg of zirconium oxychloride octahydrate (ZrOCl2·8H2O), 1190 mg of 2,3,5,6-tetrafluoroterephthalic acid, and 61 mg of benzoic acid (molar ratio to fluorine-containing ligand approximately 0.1:1) were weighed and added to 50 mL of a ternary mixed solvent of N,N-dimethylformamide / water / acetic acid in a volume ratio of 5:3:2. After thorough stirring to ensure uniform dispersion, the mixture was transferred to a 100 mL stainless steel reactor lined with polytetrafluoroethylene and subjected to a solvothermal reaction at 100 °C for 24 h. After the reaction, the mixture was allowed to cool naturally to room temperature, and the precipitate was collected by centrifugation and washed three times sequentially with N,N-dimethylformamide and methanol. The resulting solid was then vacuum-dried at 80 °C for 12 h to obtain low-defect F-UiO-66 particles.
[0061] Steps (2) to (4) are the same as in Example 1, resulting in a low-defect F-UiO-66@PAN@PEO composite solid electrolyte membrane.
[0062] Example 3: Preparation of F-UiO-66@PAN@PEO composite solid electrolyte (benzoic acid addition amount 0.5 equivalents)
[0063] Step (1): Preparation of defect-controlled F-UiO-66 particles. 1610 mg of zirconium oxychloride octahydrate (ZrOCl2·8H2O), 1190 mg of 2,3,5,6-tetrafluoroterephthalic acid, and 305 mg of benzoic acid (molar ratio to fluorine-containing ligand approximately 0.5:1) were weighed and added to 50 mL of a ternary mixed solvent of N,N-dimethylformamide / water / acetic acid in a volume ratio of 5:3:2. After thorough stirring to ensure uniform dispersion, the mixture was transferred to a 100 mL stainless steel reactor lined with polytetrafluoroethylene and subjected to a solvothermal reaction at 100 °C for 24 h. After the reaction, the mixture was allowed to cool naturally to room temperature, and the precipitate was collected by centrifugation and washed three times sequentially with N,N-dimethylformamide and methanol. The resulting solid was then vacuum-dried at 80 °C for 12 h to obtain high-defect F-UiO-66 particles.
[0064] Steps (2) to (4) are the same as in Example 1, resulting in a high-defect-degree F-UiO-66@PAN@PEO composite solid electrolyte membrane.
[0065] Comparative Example 1: Preparation of ordinary UiO-66@PAN@PEO composite solid electrolyte
[0066] The difference from Example 1 is that 1,4-phthalic acid is used instead of 2,3,5,6-tetrafluoroterephthalic acid in step (1), and benzoic acid is not added to prepare ordinary non-fluorinated UiO-66 particles; the remaining steps are the same as in Example 1.
[0067] Comparative Example 2: Preparation of PAN@PEO Composite Solid Electrolyte
[0068] The difference from Example 1 is that F-UiO-66 particles are not added in step (2), and only PAN and N,N-dimethylformamide are used to prepare the electrospinning precursor solution to obtain a pure PAN nanofiber membrane; the remaining steps are the same as in Example 1.
[0069] Morphology and elemental distribution characterization: The morphology of the defect-controlled F-UiO-66 particles and F-UiO-66@PAN composite nanofiber membranes obtained in Examples 1 to 3 was observed using scanning electron microscopy. The results show (e.g.) Figure 3 As shown), the defect-controlled F-UiO-66 particles exhibit a polyhedral morphology; when the mass ratio of F-UiO-66 particles, PAN, and N,N-dimethylformamide is 2:1:10, the composite membrane has a continuously cross-linked nanofiber network, and the F-UiO-66 particles are relatively uniformly distributed on the surface of the PAN fibers and in the pores between the fibers (as shown). Figure 4 As shown). EDS elemental distribution results show that C, N, O, Zr, and F elements are uniformly distributed in the composite membrane, proving that F-UiO-66 forms a uniform composite structure with PAN fibers (as shown). Figure 5 (As shown).
[0070] Structural and chemical characterization: XRD was used to characterize the crystal structure of defect-controlled F-UiO-66 particles and F-UiO-66@PAN composite nanofiber membranes (e.g., Figure 6 As shown), the surface elements and chemical bonds of the F-UiO-66@PAN composite nanofiber membrane were characterized using XPS (e.g., Figure 7 (As shown). The results show that the defect-regulated F-UiO-66 retains the characteristic structure of Zr-based MOFs in the composite fiber membrane; compared with pure UiO-66, the diffraction peaks of the defect-regulated F-UiO-66 are slightly broadened, indicating that the introduction of benzoic acid increases the degree of framework defects. The presence of F 1s signal and CF-related peaks in F-UiO-66@PAN indicates that the fluorinated ligand was successfully introduced and stably exists in the composite framework.
[0071] Ionic conductivity testing: The F-UiO-66@PAN@PEO composite solid electrolytes obtained in Examples 1 to 3 were assembled into stainless steel sheet / electrolyte / stainless steel sheet structures, respectively. The impedance at different temperatures from 30°C to 80°C was measured using the AC impedance method, and the ionic conductivity was calculated based on the electrolyte thickness and effective contact area. The results (e.g.) Figure 8 As shown, the amount of benzoic acid added affects the defect structure and ion transport performance of F-UiO-66; the composite solid electrolyte with 0.3 equivalents of benzoic acid added in Example 1 has an ionic conductivity of 0.0726 mS·cm at 30°C. -1 The ionic conductivity at 80℃ is 1.021 mS·cm. -1 The composite electrolyte exhibits superior ion transport performance. A suitable number of defect structures can increase lithium-ion active sites, thereby improving ion conduction efficiency; however, excessive defects may lead to decreased framework stability, which is detrimental to ion transport. Notably, the ionic conductivity of the composite electrolyte significantly increases with increasing temperature, indicating its good ion conduction capability under high-temperature conditions. This, along with its thermal dimensional stability, ensures the safety and reliability of high-temperature battery operation.
[0072] Electrochemical stability window test: Linear sweep voltammetry was performed using a Li||Al cell. The results showed that the oxidation stability potential of the F-UiO-66@PAN@PEO composite solid electrolyte obtained in Example 1 reached 5.56 V, indicating that the synergistic effect of the F-UiO-66 filler and the PAN fiber skeleton is beneficial to improving the electrochemical stability of the composite solid electrolyte (e.g., ...). Figure 9 (As shown).
[0073] Lithium deposition / stripping stability test: The composite solid electrolytes obtained in Examples 1 to 3 were assembled into Li||Li symmetric cells as Application Examples 1-3, and constant current cycling tests were conducted at 60°C. The test results show that adjusting the amount of benzoic acid added can change the defect structure and interfacial transport characteristics of F-UiO-66; among them, the F-UiO-66@PAN@PEO electrolyte with 0.3 equivalents of benzoic acid added in Example 1 showed stable performance at 0.1 mA cm⁻¹. -2 It can cycle stably for more than 3000 hours and maintain a low polarization voltage at stepped current densities (e.g., Figures 10-11 (As shown).
[0074] Full cell performance testing: The F-UiO-66@PAN@PEO composite solid electrolyte obtained in Example 1 was assembled into a LiFePO4||Li full cell as Application Example 4, and charge-discharge tests were conducted at 60°C. This full cell maintained a capacity of 147.1 mAh g⁻¹ after 100 cycles at 0.1 C. -1 The discharge capacity remained at 145.6 mAh g after 200 cycles. -1 It exhibits good capacity retention capabilities (e.g.) Figure 12 (As shown).
[0075] Thermal dimensional stability test: The composite solid electrolyte membranes obtained in Examples 1 to 3 were heat-treated in air at 100°C, 140°C, and 180°C for 2 h, respectively. The results showed (e.g.) Figure 13 As shown in the figure, the F-UiO-66@PAN@PEO membrane with 0.3 equivalents of benzoic acid added obtained in Example 1 exhibited area retention rates of 95%, 88%, and 86% at the above temperatures, respectively, all of which were superior to the UiO-66@PAN@PEO of Comparative Example 1 (90%, 83%, and 73%, respectively) and PAN@PEO of Comparative Example 2 (80%, 73%, and 65%, respectively). This indicates that the defect-controlled F-UiO-66 particles and the PAN fiber network work synergistically to significantly improve the thermal dimensional stability of the composite solid electrolyte membrane.
[0076] Thermal stability mechanism analysis: The excellent thermal dimensional stability of the F-UiO-66@PAN@PEO composite solid electrolyte described in this application is due to the synergistic effect of multiple factors, the specific mechanism of which is as follows:
[0077] (1) Chemical bond energy level: CF bond has a high bond energy, much higher than CH bond and CO bond. The introduction of fluorine-containing ligands results in a large number of high-bond-energy CF bonds in the MOF framework, which significantly increases the thermal decomposition energy barrier of the framework, making it more difficult for fluorinated UiO-66 to undergo chemical bond breakage and structural collapse at high temperatures.
[0078] (2) Framework stability: The UiO-66 type MOF uses the Zr6O4(OH)4 metal cluster as the structural unit. The Zr-O bond has high bond energy and chemical stability, and its framework structure has excellent heat resistance. Fluorination modification further enhances the thermal stability of the ligands, making the entire MOF particle have excellent heat resistance.
[0079] (3) Physical support layer: The PAN electrospun nanofiber network forms a continuous three-dimensional skeleton structure with high heat distortion temperature and mechanical strength. As a physical support, this fiber network can effectively limit the flow, softening and macroscopic shrinkage of the PEO matrix at high temperature and maintain the dimensional integrity of the electrolyte membrane.
[0080] (4) Interface interaction level: There is a dipole-dipole interaction between the CF bond on the surface of the fluorinated MOF particles and the PEO molecular chain. These interface interactions can restrict the thermal motion of the PEO molecular chain, increase the thermal deformation temperature of the PEO phase, and thus enhance the thermal dimensional stability of the entire composite system.
[0081] (5) Defect regulation level: Although the ligand defects introduced by benzoic acid as a regulator increase the disorder of the framework to a certain extent, an appropriate amount of defects can enhance the interfacial bonding force between MOF particles and PEO matrix, further suppress thermal slip and debonding at the interface, which is beneficial to maintaining the integrity of the composite structure at high temperature.
[0082] As can be seen from the above embodiments and test results, this application prepares defect-controlled fluorinated UiO-66 by using zirconium oxychloride as the zirconium source and benzoic acid as the modifier via a solvothermal method, and then constructs it by combining it with PAN electrospun porous fiber membrane and PEO / LiTFSI polymer electrolyte phase. This method can improve ion transport capacity, electrode interface stability and thermal dimensional stability while maintaining membrane structure stability, and is suitable for high-safety solid-state lithium metal batteries.
[0083] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A solid electrolyte, characterized in that: It includes a PAN electrospun nanofiber skeleton, defect-controlled fluorinated UiO-66 particles anchored or dispersed on the PAN electrospun nanofiber skeleton, and a PEO / LiTFSI polymer electrolyte phase filling the pores of the PAN electrospun nanofiber skeleton. The defect-controlled fluorinated UiO-66 particles are distributed along the surface of the PAN electrospun nanofiber skeleton or the inter-fiber pores, forming a continuous metal-organic framework enriched ion transport interface. The defect-regulated fluorinated UiO-66 particles contain ligand defect sites generated by benzoic acid regulation, which provide additional active sites for lithium ion adsorption and transport.
2. The solid electrolyte according to claim 1, characterized in that: After heat treatment in air at 180°C for 2 hours, the solid electrolyte retains an area of not less than 85%; and its ionic conductivity at 80°C is not less than 1.0 mS·cm. -1 The composite solid electrolyte exhibits an ionic conductivity of not less than 0.07 mS·cm at 30°C. -1 The oxidation stability potential is not lower than 5.5 V.
3. A method for preparing a solid electrolyte according to claim 1, characterized in that, Includes the following steps: (1) Zirconium oxychloride, fluorine-containing organic ligands and benzoic acid were added to a mixed solvent, and after solvothermal reaction, separation, washing and drying, defect-controlled fluorinated UiO-66 particles were obtained. (2) The defect-controlled fluorinated UiO-66 particles, PAN and the first organic solvent are mixed to obtain an electrospinning precursor solution; the electrospinning precursor solution is electrospinned and dried to obtain an F-UiO-66@PAN porous composite nanofiber membrane. (3) Dissolve polyethylene oxide and LiTFSI in a second organic solvent to obtain a polymer electrolyte solution; (4) The polymer electrolyte solution is impregnated or cast into the F-UiO-66@PAN porous composite nanofiber membrane and dried to obtain F-UiO-66@PAN@PEO composite solid electrolyte.
4. The method for preparing a solid electrolyte according to claim 3, characterized in that: In step (1), zirconium oxychloride is zirconium oxychloride octahydrate, the fluorinated organic ligand is 2,3,5,6-tetrafluoroterephthalic acid, and the molar ratio of benzoic acid to the fluorinated organic ligand is (0.1-0.5):1; the mixed solvent is a ternary mixed solvent of N,N-dimethylformamide, water and acetic acid, and the volume ratio of the three is (4-6):(2-4):(1-3); the solvothermal reaction temperature is 90-120℃, and the reaction time is 18-30 h.
5. The method for preparing a solid electrolyte according to claim 3, characterized in that: In the defect-regulated fluorinated UiO-66 particles obtained in step (1), benzoic acid is introduced as a coordination regulator to the defect sites of the missing ligands, with a defect degree of 5%-15%.
6. The method for preparing a solid electrolyte according to claim 3, characterized in that: In step (2), the first organic solvent is N,N-dimethylformamide, and the mass ratio of the defect-controlled fluorinated UiO-66 particles, PAN and the first organic solvent is (1-3):(0.5-1.5):(8-12).
7. The method for preparing a solid electrolyte according to claim 3, characterized in that: In step (2), the electrospinning voltage is 2-15 kV and the distance from the nozzle to the receiver is 10-18 cm. The fiber membrane obtained after electrospinning is first dried at 50-80℃ and then vacuum dried at 120-170℃.
8. The method for preparing a solid electrolyte according to claim 3, characterized in that: In step (3), the second organic solvent is acetonitrile, and the polymer electrolyte solution contains polyethylene oxide and Li + The molar ratio is (8-15):1; polyethylene oxide and LiTFSI are stirred and dissolved at 60-80℃, and then stirred and degassed at 35-50℃.
9. The method for preparing a solid electrolyte according to claim 3, characterized in that: In step (4), the polymer electrolyte solution is impregnated or cast into the F-UiO-66@PAN porous composite nanofiber membrane in an inert atmosphere and dried at 50-70°C to remove the solvent.
10. A solid-state lithium metal battery, characterized in that, Includes the solid electrolyte as described in any one of claims 1-9.